Pan-Genome-Based Characterization of the SRS Transcription Factor Family in Foxtail Millet - Ruimiao Li; Cuiyun Lei; Qiang Zhang; Xiaomeng Guo; Xiting Cui; Xingchun Wang; Xukai Li; Jianhua Gao (Plants)
The Short Internodes-Related Sequence (SRS) family, a class of plant-specific transcription factors crucial for diverse biological processes, was systematically investigated in foxtail millet using pan-genome data from 110 core germplasm resources as well as two high-quality genomes (xm and Yu1). We identified SRS members and analyzed their intra-species distribution patterns, including copy number variation (CNV) and interchromosomal translocations. A novel standardized nomenclature (Accession_SiSRSN[.n]_xDy or xTy) was proposed to unify gene family nomenclature, enabling the direct visualization of member number variation across germplasms and the identification of core/variable members while highlighting chromosomal translocations. Focusing on the two high-quality genomes, both harboring six core SRS members, we performed whole-genome collinearity analysis with Arabidopsis, rice, maize, soybean, and green foxtail. Ka/Ks analysis of collinear gene pairs revealed purifying selection acting on SiSRS genes. Promoter analysis identified abundant stress-responsive cis-elements. Among core members, the xm_SiSRS5 gene exhibited the highest expression during vegetative growth but showed significant downregulation under drought and salt stress, suggesting its role as a key negative regulator in abiotic stress responses. This study demonstrates the utility of pan-genomics in resolving gene family dynamics and establishes SiSRS5 as a critical target for stress tolerance engineering in foxtail millet.